PENGEMBANGAN MEDIA PEMBELAJARAN PENDIDIKAN KESEHATAN MELALUI KARTU SEHAT - Loren Fibrilia P; Endang Sri Hanani; Tommy Soenyoto (Universitas Negeri Semarang, 2016)
This study aims to produce the model of health education through health cards for class VIII SMP Islam Al Madina Semarang. This research is a development which refers to the model of development of Brog and Gall, with steps as follows: 1) conduct a needs analysis of the results of field observation, interviews and review of the literature, 2) develop initial product, 3) expert evaluation of physical education and expert teaching physical education, as well as the trial I (n = 12), 4) revision of the initial product, 5) test II (N = 29), 6) a revision of the final product, 7) the final results of the health card. The results of this study is the validation data of the experts of healthy education and two experts learning in the initial product before the test I, the trials I, and trial II, the average results of the assessment are expert healthy education 79% (good) and learning experts 86,5% (good), the tests I obtained the results of the questionnaire the average percentage of selection of an appropriate response 81% (good). As for the second test of the questionnaire results the average percentage corresponding answer choice 92.75% (excellent). Based on the results, it can be concluded that the health card media is completely unfit for learning physical education in improving students' knowledge of health education for the students of class VIII SMP Islam Al Madina Semarang.